Sodium-ion battery positive electrode precursor material and preparation method thereof, positive electrode material, sodium-ion battery and electric equipment

By optimizing the structure and preparation method of the positive electrode precursor material of sodium ion battery, the problems of uneven phase change and diffusion rates of existing materials under high pressure are solved, and higher cycle stability and electrochemical performance are achieved.

CN119683707AActive Publication Date: 2025-03-25SHENZHEN BTR NEW ENERGY TECH RES INST CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510192946.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-21
Publication Date
2025-03-25
Estimated Expiration
2045-02-21

AI Technical Summary

Technical Problem

The existing sodium ion battery positive electrode materials have bad phase change under high pressure, resulting in rapid attenuation of capacity, and the precursor material has poor spherical shape, and the sodium ion diffusion rate is uneven, which affects long cycle performance.

Method used

A sodium ion battery positive electrode precursor material is provided, and the arc and thickness of the primary particles are provided to satisfy a specific relationship, and the preparation method of the material includes performing a stirring reaction in an inert atmosphere, controlling the pH value drop and constant to achieve a uniform dispersion and layer-mallocated structure.

Benefits of technology

By optimizing the structure of the precursor material, it improves sodium ion absorption and diffusion efficiency, reduces the material surface energy, prolongs cycling stability, and forms a cathode material with high crystallinity at low sintering temperatures, with better performance and lower cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119683707A_ABST
    Figure CN119683707A_ABST
Patent Text Reader

Abstract

The invention provides a sodium-ion battery positive electrode precursor material and a preparation method thereof, a positive electrode material, a sodium-ion battery and electric equipment, and relates to the field of sodium-ion batteries. The vertical distance d from the fitted arc at the top end of the primary particle of the sodium ion battery positive electrode precursor material to the cross section and the thickness s of the primary particle meet the relational expression that d / s is more than or equal to 1 / 8 and less than or equal to 1 / 4. The sodium ion battery positive electrode precursor material has few gaps but is tightly attached, has thick primary particles but is stacked in a staggered manner, and has better sodium ion absorption.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of sodium ion batteries, and in particular to a sodium ion battery positive electrode precursor material and a preparation method thereof, a positive electrode material, a sodium ion battery and an electrical device. Background Art

[0002] Sodium-ion batteries (SIBs) are considered one of the most likely candidates to replace current commercial lithium-ion batteries due to the abundance of sodium, low cost, and similar properties to lithium-ion batteries.

[0003] Sodium ion transition metal oxides (Na x TMO 2 ; x≤1; where TM is a transition metal such as Ni, Co, Mn, Fe, Cu, Cr, etc.) is a promising cathode material for SIBs, depending on the coordination environment of Na ions (triangular prism or octahedral position) and the TMO in the repeated stacking unit. 2 The number of layers, Na layered oxides are mainly divided into P2 and O3 types; P2 type positive electrode has a larger Na + The P2-type cathode has a higher diffusion channel and better kinetic performance, but the Na content in the P2-type cathode is insufficient, resulting in a lower theoretical specific capacity. In addition, the harmful phase transition from P2 to O2 under high pressure is accompanied by a significant volume change, resulting in rapid capacity decay. In contrast, the initial Na content of the O3-phase cathode material is high, corresponding to a higher theoretical capacity, which requires the introduction of a large amount of sodium source during the solid-phase sintering stage. During the sintering process, Na + Penetrating from the (010) surface of the precursor to the inside, optimizing the (010) exposed surface of the precursor can expand the ion transmission channel and reduce the residual alkali on the surface of the material.

[0004] Precursor is a key intermediate product in the battery industry chain that connects upstream raw material resources and downstream positive electrode materials. In theory, the crystal structure of the precursor can be inherited by the positive electrode material, and its physical and chemical indicators (such as elemental composition, particle size, tap density, specific surface area, surface morphology, crystal structure, etc.) directly affect the performance of the positive electrode material after sintering.

[0005] For example, Chinese patent CN115072805B reports a sodium ion battery positive electrode material precursor composed of a cross-linked sheet structure. The sodium ion battery positive electrode material assembled battery prepared by the precursor has high specific capacitance, first-cycle coulomb efficiency and cycle stability. However, the sphericity of the precursor material is poor. When the sodium source is introduced into the sintering, the sodium ions tend to be enriched in the depressions on the surface of the precursor sphere, resulting in uneven inward diffusion rate of the sodium ions, forming a certain sodium ion concentration gradient inside the positive electrode material, and the positive electrode performance deteriorates significantly after long cycles.

[0006] For example, Chinese patent CN118289841A reports an in-situ coated sodium ion battery positive electrode material. A low-alkalinity sodium source is used to replace part of the sodium carbonate to reduce the alkalinity and perform in-situ doping. After a sintering step, a metal oxide is used for coating. The coating layer can further reduce the residual alkali on the surface of the material. However, the introduction of multiple additives will hinder the diffusion of sodium ions to a certain extent, and the use of multi-layer coating to reduce the residual alkali will increase production costs, which is not suitable for industrialization.

[0007] Another example is Chinese patent CN117401726A, which reports a zinc-doped sodium ion battery positive electrode precursor material. By modifying the material by adding zinc, the sodium ion battery positive electrode material precursor is prepared by coprecipitation, which can increase the contact area with the electrolyte and improve the sodium ion transmission efficiency. However, the precipitation equilibrium constant of zinc ions is different from that of nickel, iron, and manganese ions, and simple mixed coprecipitation is prone to uneven element distribution.

[0008] Therefore, how to modify and regulate the precursor end, guide the optimization of the positive electrode material crystals, and obtain materials with better comprehensive performance is a problem that needs to be solved urgently. Summary of the invention

[0009] The purpose of the present application is to provide a sodium ion battery positive electrode precursor material and a preparation method thereof, a positive electrode material, a sodium ion battery and an electrical device to solve the above-mentioned problems.

[0010] To achieve the above objectives, the first aspect of the present application provides a sodium ion battery positive electrode precursor material, wherein the vertical distance d from the arc fitted at the top of the primary particle of the sodium ion battery positive electrode precursor material to the cross section and the thickness s of the primary particle satisfy the relationship: 1 / 8≤d / s≤1 / 4.

[0011] Optionally, the thickness s of the primary particles is 120nm-360nm.

[0012] Optionally, the thickness s of the primary particles and the gap width t between the primary particles satisfy the relationship: 1.0≤s / t≤7.5.

[0013] Optionally, the gap width t between the primary particles is 45nm-120nm.

[0014] Optionally, the sodium ion battery cathode precursor material satisfies at least one of the following conditions: A. The D50 of the sodium ion battery positive electrode precursor material is 7 μm-12 μm; B. The tap density TD of the sodium ion battery positive electrode precursor material is ≥ 1.4 g / cm 3 ; C. The specific surface area SSA of the sodium ion battery positive electrode precursor material is 2m 2 / g-5m 2 / g; D. The pH value of the sodium ion battery positive electrode precursor material is 8-10; E. Na in the sodium ion battery positive electrode precursor material + Content ≤200ppm, SO 4 2- Content ≤2000ppm; F. The mass content of water in the sodium ion battery positive electrode precursor material is ≤0.60%; G. The sodium ion battery cathode precursor material is spherical and / or quasi-spherical; H. The chemical formula of the sodium ion battery positive electrode precursor material is Ni a Fe b Mn c R (1-a-b-c) (OH) 2 ; Wherein, 0.1≤a≤0.4, 0<b≤0.3, 0<c≤0.7, 0.9≤a+b+c≤1, R is selected from one or more of Zn, Mg, Ti, Cu, Ca, W, Al, Co, and Zr; I. The sodium ion battery positive electrode precursor material includes an O3 type sodium ion battery positive electrode precursor material.

[0015] The second aspect of the present application provides a method for preparing the positive electrode precursor material of a sodium ion battery, comprising: In an inert atmosphere, a mixed metal salt solution, a doped metal salt solution, a complexing agent, and a precipitant are simultaneously introduced into a base liquid, a first reaction is performed under stirring, a pH value of the solution during the first reaction is controlled to continuously decrease, and then the mixed metal salt solution, the doped metal salt solution, the complexing agent, and the precipitant are introduced, and a second reaction is performed while maintaining a constant pH value to prepare the sodium ion battery positive electrode precursor material; The mixed metal salt solution includes manganese salt, nickel salt and iron salt.

[0016] Optionally, the method for preparing the sodium ion battery positive electrode precursor material satisfies at least one of the following conditions: A. the manganese salt comprises one or more of manganese sulfate, manganese chloride, manganese acetate and manganese nitrate; B. the nickel salt comprises one or more of nickel sulfate, nickel chloride, nickel acetate and nickel nitrate; C. the iron salt comprises one or more of ferrous sulfate, ferrous chloride, ferrous acetate and ferrous nitrate; D. the doped metal salt in the doped metal salt solution includes one or more of sulfate, chloride, acetate and nitrate containing the doping element; E. the complexing agent includes one or more of ammonia water, oxalic acid, citric acid or sodium citrate; F. the precipitating agent comprises one or more of sodium hydroxide, potassium hydroxide, sodium carbonate and potassium carbonate; G. the inert gas in the inert atmosphere comprises nitrogen and / or argon; H. the base liquid is a mixture of the water, the precipitant and the complexing agent; I. The pH value of the base solution is 12.00-13.00; J. The endpoint pH of the first reaction is 11.40-11.60, and the reaction time is 0.5h-1h; K. The temperature of the first reaction and the second reaction is 55-65°C; L. The pH of the second reaction is 11.40-11.60.

[0017] The third aspect of the present application provides a positive electrode material obtained by mixing and sintering the sodium ion battery positive electrode precursor material and a sodium source.

[0018] A fourth aspect of the present application provides a sodium ion battery, comprising the above-mentioned positive electrode material.

[0019] The fifth aspect of the present application provides an electrical device, including the sodium ion battery.

[0020] Compared with the prior art, the beneficial effects of this application include: The sodium ion battery positive electrode precursor material provided in the present application has few voids but is tightly fitted, and has thick primary particles but is fault-stacked (loosely stacked). After the introduction of doping elements, stratification occurs inside the primary particles of the precursor, and the exposed (010) crystal plane obtains more active sites. The surface energy of the material is reduced during sintering and melting, and it has better sodium ion absorption.

[0021] The preparation method of the sodium ion battery positive electrode precursor material provided in the present application realizes uniform dispersion of the material under stirring, and the primary nanosheet elements of the precursor primary particles co-built by the doping elements and the transition metal elements under strong stirring are evenly distributed. Due to the introduction of the doping elements with a high number of extranuclear electrons, the number of hydrogen bonds in the transition metal layer increases, the electrostatic repulsion is enhanced, and the structure of the precursor primary particles is further changed, and the primary particles become loose inside and stratified.

[0022] The positive electrode material provided in the present application can form a polycrystalline sodium positive electrode material with high crystallinity in a short insulation time and a low sintering temperature, and has the advantages of better performance, lower residual alkali, and lower cost.

[0023] The sodium ion battery and electrical equipment provided by the present application have low cost and good performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.

[0025] Figure 1 This is a schematic diagram of loosely stacked primary particles; Figure 2 for Figure 1 A local enlarged view of the red line area in the figure; Figure 3 It is a schematic diagram of dense primary particles; Figure 4 This is a schematic diagram of measuring the vertical distance d and the thickness s on the SEM image of the positive electrode precursor material of the O3 type sodium ion battery in Example 1; Figure 5 This is a schematic diagram of the gap width t and thickness s on the SEM image of the positive electrode precursor material of the O3 type sodium ion battery in Example 1; Figure 6 This is a SEM image of the O3 type sodium ion battery positive electrode precursor material provided in Example 1. DETAILED DESCRIPTION

[0026] As used herein: "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0027] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.

[0028] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values ​​and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values ​​and all integers and fractions within the range.

[0029] In these examples, parts and percentages are by mass unless otherwise indicated.

[0030] "Mass parts" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass parts of component A are a parts and the mass parts of component B are b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass parts of all components is not limited to 100 parts.

[0031] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).

[0032] Based on the above problem, the present application provides a sodium ion battery positive electrode precursor material in the first aspect, wherein the vertical distance d from the arc fitted at the top of the primary particle of the sodium ion battery positive electrode precursor material to the cross section and the thickness s of the primary particle satisfy the relationship: 1 / 8≤d / s≤1 / 4.

[0033] It should be noted that if Figure 1 or Figure 2 As shown, in the front view of the loosely stacked primary particles, the upper vertex of the primary nanosheet at the edge of the primary particle is used as the endpoint to make a cross section, and the length of this cross section is equal to the thickness s of the primary particle (thickness s refers to the average thickness of the primary particle). The primary nanosheet at the top of the primary particle is used as the differential unit, and the top of the primary particle with stacking faults can be approximately fitted into a smooth curve l. The vertical distance from the smooth curve 1 to the cross section is d. When the vertical distance d (referring to the farthest vertical distance of the primary particle) and the thickness s satisfy the above relationship, the curvature and curvature radius of the smooth curve 1 are better, and even if it is a stacking arrangement mode of the primary nanosheets, the sodium ion absorption of the primary particles can be the best; When d / s is not within the range of 1 / 8-1 / 4, such as Figure 3 As shown in the figure, when the stacking fault degree of the dense primary particles is too low or too high, it will lead to poor sodium ion absorption and poor sintering activity when it is too low; when it is too high, the positive electrode particles are fine after sintering, and the capacity release and cycle performance are deteriorated; In some embodiments, the thickness s of the primary particle is 120 nm-360 nm.

[0034] Optionally, the thickness s of the primary particle may be 120 nm, 180 nm, 240 nm, 300 nm, 360 nm or any value between 120 nm and 360 nm.

[0035] In some embodiments, the thickness s of the primary particles and the gap width t between the primary particles satisfy the relationship: 1.0≤s / t≤7.5.

[0036] Optionally, s / t can be 1.5, 2, 3, 4, 5, 6, 7 or any value between 1.0-7.5.

[0037] When the gap width t is less than 45nm, the gap between the primary particles is too small and too dense. When sintered into polycrystalline positive electrode materials, the volume of the primary particles increases, and the precursor ball is at risk of expansion, extrusion and cracking. When the gap width t is greater than 120nm, the gap between the primary particles is too large, and there may be gaps on the surface of the polycrystalline positive electrode material generated by sintering, forming electrolyte infiltration channels, resulting in a decrease in electrical performance.

[0038] When 1.0≤s / t≤7.5, the size of the primary particles and the width of the gaps between the primary particles reach a balance, and the polycrystalline positive electrode material generated by sintering has high crystallinity, a dense and seamless surface, and good electrical properties.

[0039] In some embodiments, the gap width t between the primary particles is 45 nm-120 nm.

[0040] Optionally, the gap width t between the primary particles can be 45 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 110 nm, 120 nm or any value between 45 nm and 120 nm.

[0041] In some embodiments, the sodium ion battery cathode precursor material satisfies at least one of the following conditions: A. The D50 of the sodium ion battery positive electrode precursor material is 7 μm-12 μm; Optionally, the D50 of the sodium ion battery cathode precursor material may be 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm or any value between 7 μm and 12 μm; B. The tap density TD of the sodium ion battery positive electrode precursor material is ≥ 1.4 g / cm 3 ; Optionally, the tap density TD of the sodium ion battery cathode precursor material can be 1.4 g / cm 3 , 1.5g / cm 3 , 1.6g / cm 3 , 1.7g / cm 3 , 1.8g / cm 3 , 1.9g / cm 3 , 2.0g / cm 3 Or greater than or equal to 1.4g / cm 3 Any value of C. The specific surface area SSA of the sodium ion battery positive electrode precursor material is 2m 2 / g-5m 2 / g; Optionally, the specific surface area SSA of the sodium ion battery cathode precursor material can be 2m 2 / g, 3m 2 / g, 4m 2 / g, 5m 2 / g or 2m 2 / g-5m 2 Any value between / g; D. The pH value of the sodium ion battery positive electrode precursor material is 8-10; Optionally, the pH value of the sodium ion battery cathode precursor material may be 8, 8.5, 9, 9.5, 10 or any value between 8 and 10; E. Na in the sodium ion battery positive electrode precursor material + Content ≤200ppm, SO 4 2- Content ≤2000ppm; Optionally, Na in the cathode precursor material of sodium ion battery + The content can be 100ppm, 120ppm, 140ppm, 160ppm, 180ppm, 200ppm or any value less than or equal to 200ppm. 4 2- The content may be 1000ppm, 1200ppm, 1400ppm, 1600ppm, 1800ppm, 2000ppm or any value less than or equal to 2000ppm; F. The mass content of water in the sodium ion battery positive electrode precursor material is ≤0.60%; Optionally, the mass content of water in the sodium ion battery positive electrode precursor material may be 0.40%, 0.45%, 0.50%, 0.55%, 0.60%, or any value less than or equal to 0.60%; G. The sodium ion battery cathode precursor material is spherical and / or quasi-spherical; H. The chemical formula of the sodium ion battery positive electrode precursor material is Ni a Fe b Mn c R (1-a-b-c) (OH) 2 ; Wherein, 0.1≤a≤0.4, 0<b≤0.3, 0<c≤0.7, 0.9≤a+b+c≤1, R is selected from one or more of Zn, Mg, Ti, Cu, Ca, W, Al, Co, and Zr; Exemplarily, a may be 0.1, 0.2, 0.3, 0.4 or any value between 0.1 and 0.4, b may be 0.1, 0.2, 0.3 or any value between 0.1 and 0.3, c may be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7 or any value between 0.1 and 0.7, and a+b+c may be 0.9, 0.95, 1 or any value between 0.9 and 1; I. The sodium ion battery positive electrode precursor material includes an O3 type sodium ion battery positive electrode precursor material.

[0042] It should be noted that O3-type positive electrode materials can accommodate higher sodium content and release higher specific discharge capacity, which requires the introduction of a large amount of sodium source in the sintering reaction. However, sodium has a large ionic radius and cannot be efficiently inserted / extracted from the positive electrode. A large part of the sodium will be enriched on the surface of the material and cannot be fully diffused into the lattice, causing the sodium ion content in the bulk phase of the material to deviate from the theoretical value. In addition, high residual alkali content will lead to lower capacity release, serious side reactions, and deterioration of battery performance.

[0043] The second aspect of the present application provides a method for preparing the positive electrode precursor material of a sodium ion battery, comprising: In an inert atmosphere, a mixed metal salt solution, a doped metal salt solution, a complexing agent, and a precipitant are simultaneously introduced into a base liquid, a first reaction is performed under stirring, a pH value of the solution during the first reaction is controlled to continuously decrease, and then the mixed metal salt solution, the doped metal salt solution, the complexing agent, and the precipitant are introduced, and a second reaction is performed while maintaining a constant pH value to prepare the sodium ion battery positive electrode precursor material; The mixed metal salt solution includes manganese salt, nickel salt and iron salt.

[0044] In some embodiments, the method for preparing the sodium ion battery positive electrode precursor material satisfies at least one of the following conditions: A. the manganese salt comprises one or more of manganese sulfate, manganese chloride, manganese acetate and manganese nitrate; B. the nickel salt comprises one or more of nickel sulfate, nickel chloride, nickel acetate and nickel nitrate; C. the iron salt comprises one or more of ferrous sulfate, ferrous chloride, ferrous acetate and ferrous nitrate; D. the doped metal salt in the doped metal salt solution includes one or more of sulfate, chloride, acetate and nitrate containing the doping element; E. the complexing agent includes one or more of ammonia water, oxalic acid, citric acid or sodium citrate; F. the precipitating agent comprises one or more of sodium hydroxide, potassium hydroxide, sodium carbonate and potassium carbonate; G. the inert gas in the inert atmosphere comprises nitrogen and / or argon; H. the base liquid is a mixture of the water, the precipitant and the complexing agent; I. The pH value of the base solution is 12.00-13.00; Optionally, the pH value of the base solution may be 12.0, 12.1, 12.2, 12.3, 12.4, 12.5, 12.6, 12.7, 12.8, 12.9, 13 or any value between 12.00-13.00; J. The endpoint pH of the first reaction is 11.40-11.60, and the reaction time is 0.5h-1h; Optionally, the endpoint pH of the first reaction may be 11.40, 11.45, 11.5, 11.55, 11.6 or any value between 11.40 and 11.60, and the time may be 0.5 h, 0.6 h, 0.7 h, 0.8 h, 0.9 h, 1 h or any value between 0.5 h and 1 h; It should be noted that when the pH of the first reaction continued to decrease until it reached 11.40-11.60, the supersaturation in the reactor reached a low value, the driving force for homogeneous nucleation was low, and the precursor began to grow.

[0045] K. The temperature of the first reaction and the second reaction is 55°C-65°C; Optionally, the temperature of the first reaction and the second reaction can be 55°C, 56°C, 57°C, 58°C, 59°C, 60°C, 61°C, 62°C, 63°C, 64°C, 65°C or any value between 55°C and 65°C; It should be noted that when the reaction temperature is in the range of 55°C-65°C, the primary nanosheets tend to stack along the (001) direction at higher temperatures, and the stacking density of the precursor primary particles increases.

[0046] L. The pH of the second reaction is 11.40-11.60.

[0047] Optionally, the pH of the second reaction can be 11.40, 11.45, 11.5, 11.55, 11.6 or any value between 11.40-11.60.

[0048] It should be noted that when the pH of the second reaction was maintained in the range of 11.40-11.60, stacking faults occurred during the growth and stacking of the primary nanosheets at higher pH values.

[0049] The third aspect of the present application provides a positive electrode material obtained by mixing and sintering the sodium ion battery positive electrode precursor material and a sodium source.

[0050] A fourth aspect of the present application provides a sodium ion battery, comprising the above-mentioned positive electrode material.

[0051] The fifth aspect of the present application provides an electrical device, including the sodium ion battery.

[0052] It should be noted that electrical equipment may be but is not limited to mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc.; among them, mobile devices may include but are not limited to at least one of mobile phones, laptop computers, etc.; electric vehicles may include but are not limited to at least one of pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.

[0053] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0054] In the embodiment, the reaction equipment for precipitating the positive electrode precursor material of the O3 type sodium ion battery is a 1000L closed metal reactor with three-layer blades, and the blades are all four-paddle stirring paddles with an inclination angle of 45°. The upper and lower four-paddle blades are 0.33 times the diameter of the reactor, and the middle-layer paddle blades are 0.45 times the diameter of the reactor; the positions of the upper, middle and bottom stirring paddles are 1 / 4, 2 / 4 and 3 / 4 downward from the top of the reactor, respectively. The reactor is equipped with multiple feed pipes, and the feed pipe openings of the mixed salt solution and the doped salt solution are located at the center of the interval between the middle-layer stirring paddle and the bottom-layer stirring paddle. The feed is fully and evenly mixed under the high shear action of the wide-blade middle-layer stirring paddle.

[0055] Example 1 This embodiment provides an O3 type sodium ion battery positive electrode precursor material and a preparation method thereof. The chemical formula of the precursor material is Ni 0.22 Fe 0.30 Mn 0.45 Zn 0.03 (OH) 2 , the specific preparation method is as follows: 1. Prepare mixed salt solution: Nickel sulfate hexahydrate, ferrous sulfate heptahydrate and manganese sulfate monohydrate are dispersed in pure water, and stirred continuously for 4 hours at a stirring speed of 40 r / min to prepare a nickel-iron-manganese mixed salt solution; wherein the total concentration of metal ions is 2 mol / L, and the mass ratio is Ni:Fe:Mn=22:30:45. The prepared mixed salt solution is filtered, demagnetized, and temporarily stored in a transfer tank; 2. Prepare doped salt solution: Disperse zinc sulfate heptahydrate in pure water, add 30% ammonia solution to the zinc salt solution, the volume ratio of the zinc salt solution to the ammonia solution is 40:1, and stir continuously for 4 hours at a stirring speed of 40 r / min to prepare a doped salt solution, in which the total concentration of metal ions is 1 mol / L; filter and demagnetize the prepared doped zinc salt solution, and temporarily store it in a transfer tank; 3. Prepare the reaction base solution: In a 1000L sealed metal reactor, add pure water until the reactor is nearly full and introduce N 2 Protection, nitrogen flow rate is 10L / min, add 500mL hydrazine hydrate to the reactor, set the stirring speed to 200r / min and continue stirring for 1h; add 10M sodium hydroxide solution and 30% ammonia solution to the reactor, adjust the ammonia concentration to 6g / L, and adjust the pH value to the offline value between 12.20-12.30; 4. Start the reaction: Set the stirring speed of the reaction equipment (reactor) to 300r / min, heat the reactor to 60°C by circulating water heating, and flow the mixed salt solution obtained in step 1 and step 2, the doped zinc salt solution, the complexing agent and the precipitant into the reactor in parallel, wherein the flow rate of the mixed salt solution is 60L / h, and the flow rate of the doped zinc salt solution is 1.86L / h. Under the protection of inert gas, control the pH value in the reactor to continue to decrease within 30 minutes, and test it at 50°C with a Leici PHSJ-4F pH meter. After the pH in the reactor is adjusted to 11.60, it stops decreasing, and continue to pass the mixed salt solution, doped salt solution, precipitant, and complexing agent to keep the pH within the range of 11.60±3, and stop when D50=8μm; 5. Post-processing: The reaction slurry of step 4 was centrifuged and the mother liquor was filtered out, first washed with 0.1 mol / L sodium hydroxide solution for 2 h, then washed with hot pure water for 10 h, taken out, dried in a 120°C oven for 12 h, and then passed through a 325-mesh sieve to obtain an O3 type sodium ion battery positive electrode precursor material.

[0056] The morphology of the O3 type sodium ion battery cathode precursor material is as follows Figure 4 As shown, Figure 4 The upper vertex of the primary nanosheet at the edge of the primary particle is used as the endpoint to draw a cross section. The length of this cross section is equal to the thickness s of the primary particle. The distance from the fitted arc to the cross section is the vertical distance d. The data of the vertical distance d and the thickness s are shown in Table 1.

[0057] The schematic diagram of the gap width t and thickness s of the O3 type sodium ion battery positive electrode precursor material is as follows Figure 5 As shown; Figure 6 This is the SEM image of the positive electrode precursor material of O3 type sodium ion battery; The physical properties of the O3 type sodium ion battery positive electrode precursor material are shown in Table 2.

[0058] This embodiment also provides a positive electrode material. The O3 type sodium ion battery positive electrode precursor material obtained in the above step 5 and sodium carbonate are weighed and mixed evenly in a molar ratio of 1:0.98, and then placed in a box furnace for sintering, and the temperature is raised to 900°C at a rate of 5°C / min, and kept at this temperature for 16 hours, and then naturally cooled to room temperature to obtain a positive electrode material.

[0059] Example 2 The process parameters are different from those in Example 1 as follows: during the reaction start-up process of the positive electrode precursor material of the O3 type sodium ion battery in step 4, the pH in the kettle is adjusted to 11.40 and then stops decreasing, and then the mixed salt solution, the doping salt solution, the precipitant and the complexing agent are introduced.

[0060] Example 3 The process parameters are different from those in Example 1 as follows: during the reaction of the positive electrode precursor material of the O3 type sodium ion battery in step 4, the pH in the kettle is adjusted to 11.50 and then stops decreasing, and then a mixed salt solution, a doping salt solution, a precipitant, and a complexing agent are introduced, and the reactor is heated to 65° C. by circulating water heating.

[0061] Example 4 The process parameters are different from those in Example 1 as follows: During the process of starting the reaction of the positive electrode precursor material of the O3 type sodium ion battery in step 4, the reactor is heated to 65° C. by circulating water heating.

[0062] Example 5 The process parameters are different from those in Example 1 as follows: during the reaction of the positive electrode precursor material of the O3 type sodium ion battery in step 4, the pH in the kettle is adjusted to 11.40 and then stops decreasing, and then a mixed salt solution, a doping salt solution, a precipitant, and a complexing agent are introduced, and the reactor is heated to 55° C. by circulating water heating.

[0063] Comparative Example 1 The process parameters are different from those of Example 1 in that during the reaction initiation process of the precursor material in step 4, the pH value is not adjusted, and the mixed salt solution, the doping salt solution, the precipitant, and the complexing agent are directly introduced until the precursor material with the target particle size is obtained.

[0064] Comparative Example 2 The process parameters are different from those in Example 1 as follows: during the reaction start-up process of the precursor material in step 4, the pH value is adjusted to 11.8, and then a mixed salt solution, a doping salt solution, a precipitant, and a complexing agent are introduced until a precursor material with a target particle size is obtained.

[0065] Comparative Example 3 The process parameters are different from those in Example 1 as follows: during the reaction start-up process of the precursor material in step 4, the pH value is adjusted to 11.2, and then a mixed salt solution, a doping salt solution, a precipitant, and a complexing agent are introduced until a precursor material with a target particle size is obtained.

[0066] Comparative Example 4 The process parameters differ from those of Example 1 in that during the process of starting the reaction of the precursor material in step 4, the reactor is heated to 70° C. by circulating water heating.

[0067] Comparative Example 5 The process parameters differ from those of Example 1 in that during the process of starting the reaction of the precursor material in step 4, the reactor is heated to 50° C. by circulating water heating.

[0068] Comparative Example 6 The process parameters are different from those in Example 1 in that the pH value of the base solution is 13.2.

[0069] The data of the vertical distance d and thickness s of the precursors provided in the above-mentioned embodiments and comparative examples are shown in Table 1.

[0070] Table 1 Data of vertical distance d, thickness s, and gap width t

[0071] The physical property data of the precursors provided in the above examples and comparative examples are shown in Table 2.

[0072] Table 2 Physical properties data

[0073] The precursors provided in the above examples and comparative examples were subjected to ICP testing, and the results are shown in Table 3.

[0074] Table 3 ICP test

[0075] Electrochemical performance test: The layered oxide positive electrode material was prepared into a positive electrode sheet and the battery was tested for electrochemical performance. The mass percentage of the positive electrode material, binder, and conductive agent in the positive electrode slurry was 80:1:1. The conductive agent used was sp, the binder was PVDF, the current collector used was aluminum foil, the battery shell model was CR2032, and the electrolyte was NaPF6-diethylene glycol dimethyl ether (DIGLYME) electrolyte. The buckle charge and discharge cycle test was carried out at 2.0-4.0V. The test results are shown in Table 4. The 0.2C discharge capacity is 147mAh / g, the reversible specific capacity at 1C rate is 139mAh / g, and the cycle retention rate of 300 weeks is 95%. The specific results are shown in Table 4.

[0076] Table 4 Electrochemical performance test

[0077] analyze: By comparing all the embodiments and all the comparative examples, it can be seen that when 0.125≤d / s≤0.25, the electrical properties such as discharge capacity and cycle retention rate are better released.

[0078] Compared with Example 4 and Example 5, the discharge capacity and cycle retention rate of Examples 1, 2, and 3 are better, indicating that on the basis of satisfying 0.125≤d / s≤0.25, controlling the thickness s between 120nm-360nm can further improve the discharge capacity and cycle retention rate.

[0079] Combining Table 1 and Table 4, it can be seen that the discharge capacity and cycle retention rate are better when 0.125≤d / s≤0.25 and 1.0≤s / t≤7.5 are satisfied at the same time. Furthermore, on the basis of satisfying 0.125≤d / s≤0.25 and 1.0≤s / t≤7.5, when the gap width t is 45nm-120nm, the electrical properties such as discharge capacity and cycle retention rate are better released.

[0080] Based on the test results of the above embodiments and comparative examples, it can be seen that embodiments 1-3 satisfy 0.125≤d / s≤0.25, 1.0≤s / t≤7.5, thickness s is 120nm-360nm, and gap width t is 45nm-120nm, and the electrical properties such as discharge capacity and cycle retention rate are released better; in embodiment 4, because the primary particle thickness s is higher than 360nm, s / t=7.33 belongs to the upper edge of the range [1.0,7.5], resulting in a larger positive electrode grain size, a risk of expansion and extrusion, and poor crystallinity; in embodiment 5, because the primary particle thickness s is lower than 120nm, the gap width t=113nm belongs to the upper edge of the 45nm-120nm interval, which leads to a smaller positive electrode grain size; therefore, the electrical properties such as discharge capacity and cycle retention rate of the two are slightly worse than those of embodiments 1-3. Since the pH value of Comparative Examples 1, 2, and 6 is set higher than 11.60, the particle size D50 is small, the thickness s and d / s values ​​do not meet the requirements, and the electrochemical performance is poor; since the pH value of Comparative Example 3 is set lower than 11.40, the s value is small, d / s is greater than 0.25, and the electrochemical performance is poor; since the reaction temperature of Comparative Examples 4 and 5 is not in the range of 55-65°C, the thickness s and d / s values ​​do not meet the requirements, and the electrochemical performance is poor.

[0081] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

[0082] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.

Claims

1. A sodium ion battery positive electrode precursor material, characterized in that: The vertical distance d from the arc fitted at the top of the primary particle of the sodium ion battery positive electrode precursor material to the cross section and the thickness s of the primary particle satisfy the relationship: 1 / 8≤d / s≤1 / 4.

2. The sodium ion battery positive electrode precursor material according to claim 1, characterized in that: The thickness s of the primary particles is 120 nm to 360 nm.

3. The sodium ion battery positive electrode precursor material according to claim 2, characterized in that: The thickness s of the primary particles and the gap width t between the primary particles satisfy the relationship: 1.0≤s / t≤7.

5.

4. The sodium ion battery positive electrode precursor material according to claim 3, characterized in that: The gap width t between the primary particles is 45nm-120nm.

5. The sodium ion battery positive electrode precursor material according to any one of claims 1 to 4, characterized in that: At least one of the following conditions is met: A. The D50 of the sodium ion battery positive electrode precursor material is 7 μm-12 μm; B. The tap density TD of the sodium ion battery positive electrode precursor material is ≥ 1.4 g / cm 3 ; C. The specific surface area SSA of the sodium ion battery positive electrode precursor material is 2m 2 / g-5m 2 / g; D. The pH value of the sodium ion battery positive electrode precursor material is 8-10; E. Na in the sodium ion battery cathode precursor material + Content ≤200ppm, SO4 2- Content ≤2000ppm; F. The mass content of water in the sodium ion battery positive electrode precursor material is ≤0.60%; G. The sodium ion battery cathode precursor material is spherical and / or spherical; H. The chemical formula of the sodium ion battery positive electrode precursor material is Ni a Fe b Mn c R (1-a-b-c) (OH)2; wherein 0.1≤a≤0.4, 0<b≤0.3, 0<c≤0.7, 0.9≤a+b+c≤1, and R is selected from one or more of Zn, Mg, Ti, Cu, Ca, W, Al, Co, and Zr; I. The sodium ion battery positive electrode precursor material includes an O3 type sodium ion battery positive electrode precursor material.

6. A method for preparing a sodium ion battery positive electrode precursor material according to any one of claims 1 to 5, characterized in that: include: In an inert atmosphere, a mixed metal salt solution, a doped metal salt solution, a complexing agent, and a precipitant are simultaneously introduced into a base liquid, a first reaction is performed under stirring, a pH value of the solution during the first reaction is controlled to continuously decrease, and then the mixed metal salt solution, the doped metal salt solution, the complexing agent, and the precipitant are introduced, and a second reaction is performed while maintaining a constant pH value to prepare the sodium ion battery positive electrode precursor material; The mixed metal salt solution includes manganese salt, nickel salt and iron salt.

7. The method for preparing a positive electrode precursor material for a sodium ion battery according to claim 6, characterized in that: At least one of the following conditions is met: A. the manganese salt comprises one or more of manganese sulfate, manganese chloride, manganese acetate and manganese nitrate; B. the nickel salt comprises one or more of nickel sulfate, nickel chloride, nickel acetate and nickel nitrate; C. the iron salt comprises one or more of ferrous sulfate, ferrous chloride, ferrous acetate and ferrous nitrate; D. the doped metal salt in the doped metal salt solution includes one or more of sulfate, chloride, acetate and nitrate containing the doping element; E. the complexing agent includes one or more of ammonia water, oxalic acid, citric acid or sodium citrate; F. the precipitating agent comprises one or more of sodium hydroxide, potassium hydroxide, sodium carbonate and potassium carbonate; G. the inert gas in the inert atmosphere comprises nitrogen and / or argon; H. the base liquid is a mixture of the water, the precipitant and the complexing agent; I. The pH value of the base solution is 12.00-13.00; J. The endpoint pH of the first reaction is 11.40-11.60, and the reaction time is 0.5h-1h; K. The temperature of the first reaction and the second reaction is 55°C-65°C; L. The pH of the second reaction is 11.40-11.

60.

8. A positive electrode material, characterized in that The sodium ion battery positive electrode precursor material is obtained by mixing and sintering the sodium ion battery positive electrode precursor material according to any one of claims 1 to 5 and a sodium source.

9. A sodium ion battery, characterized in that: Comprising the positive electrode material as claimed in claim 8.

10. An electrical device, characterized in that: Including the sodium ion battery as described in claim 9.

Citation Information

Patent Citations

  • Sodium ion battery positive electrode material precursor and preparation method thereof, and preparation method of sodium ion battery positive electrode material

    CN115072805B

  • Zinc-doped sodium ion battery positive electrode material precursor and preparation method thereof

    CN117401726A

  • Method for coating sodium ion battery positive electrode material in situ and sodium ion battery positive electrode material

    CN118289841A

  • Dendritic positive electrode material precursor and preparation method thereof, lithium ion battery positive electrode material, lithium ion battery and electric equipment

    CN116282207A

  • Sodium ion battery, positive electrode material and precursor thereof, and preparation method of positive electrode material and precursor

    CN116375111A